2020
DOI: 10.1001/jama.2020.1707
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Doxorubicin Plus Olaratumab vs Doxorubicin Plus Placebo on Survival in Patients With Advanced Soft Tissue Sarcomas

Abstract: IMPORTANCEPatients with advanced soft tissue sarcoma (STS) have a median overall survival of less than 2 years. In a phase 2 study, an overall survival benefit in this population was observed with the addition of olaratumab to doxorubicin over doxorubicin alone.OBJECTIVE To determine the efficacy of doxorubicin plus olaratumab in patients with advanced/metastatic STS.DESIGN, SETTING, AND PARTICIPANTS ANNOUNCE was a confirmatory, phase 3, double-blind, randomized trial conducted at 110 sites in 25 countries fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
184
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 222 publications
(191 citation statements)
references
References 19 publications
7
184
0
Order By: Relevance
“…This CSC phenotype was inhibited by the downregulation of PDGFR-α/β levels [44]. Nonetheless, the inhibition of PDGFRα with olaratumab (a human IgG1 antibody targeting PDGFRα) did not showed an enhancement of chemotherapy activity in advanced STS; the phase 3 clinical trial testing the combination of olaratumab and doxorubicin versus doxorubicin did not meet its primary endpoint [7]. Correlative studies associated with this trial are expected, in order to understand if PDGFRβ signaling pathway could have a role in tumor progression after PDGFRα inhibition and to identify those patients who could benefit from doxorubicin plus olaratumab combination.…”
Section: Pdgfrα and Pdgfrβmentioning
confidence: 99%
See 1 more Smart Citation
“…This CSC phenotype was inhibited by the downregulation of PDGFR-α/β levels [44]. Nonetheless, the inhibition of PDGFRα with olaratumab (a human IgG1 antibody targeting PDGFRα) did not showed an enhancement of chemotherapy activity in advanced STS; the phase 3 clinical trial testing the combination of olaratumab and doxorubicin versus doxorubicin did not meet its primary endpoint [7]. Correlative studies associated with this trial are expected, in order to understand if PDGFRβ signaling pathway could have a role in tumor progression after PDGFRα inhibition and to identify those patients who could benefit from doxorubicin plus olaratumab combination.…”
Section: Pdgfrα and Pdgfrβmentioning
confidence: 99%
“…Doxorubicin is the backbone for the first-line treatment of metastatic Soft-Tissue Sarcomas (STS). The combination of doxorubicin with other drugs, such as Olaratumab, palifosfamide or evofosfamide, among others have been evaluated in several comparative clinical trials against doxorubicin; however, no significant survival improvement was detected when compared with the single agent [7][8][9]. In spite of initial drug activity, patients finally progress in the majority of the cases.…”
Section: Introductionmentioning
confidence: 99%
“…Continued approval was contingent upon verification of clinical benefit in a confirmatory trial; however, the results of the phase 3 trial, ANNOUNCE, did not confirm a clinical benefit for olaratumab combined with doxorubicin compared with doxorubicin monotherapy in patients with advanced or metastatic STS. Hence, olaratumab was no longer recommended for treatment of advanced STS as of January 2019 [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Median overall survival of total soft tissue sarcomas or leiomyosarcoma alone was not significantly different (Total STS 20.4 vs. 19.7 months, leiomyosarcoma 21.6 vs. 21.9 months). They concluded that patients with advanced soft tissue sarcoma have a median overall survival of fewer than 2 years and adding olaratumab to doxorubicin does not improve the overall survival (26).…”
Section: Targeted Therapymentioning
confidence: 99%